Ide Bernegara dalam Konstitusi Indonesia: Rekonstruksi Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 Pascaamandemen - Rosadi, Otong (Universitas Muhammadiyah Sumatera Barat, 2018)
This article tries to answer the question of whether the idea of the state underlying the amendment of the 1945 Constitution? Then how to put this need in the context of (re) construction of statehood in the future. This writing is a description of the analysis with the normative approach of philosophical and juridical. The conclusion of this article states that the amendment of the 1945 Constitution, which was originally expected to improve the state administration system and state life, has actually reduced the ideas of the state that had originally been arranged systematically and directed by the founders of the state. The fifth amendment of the 1945 Constitution should be placed as the great effort of the Indonesian nation to restore the 1945 Constitution to its authenticity, as the document of the establishment of the State, the milestone of the nation's achievement / goal, the ideals and goals of the state, as well as the philosophy, values, a fundamental constitution.